A comparison of teaching tacts with and without background stimuli on acquisition and generality. (10th December 2019) - Mitteer, Daniel R.; Luczynski, Kevin C.; McKeown, Ciobha A.; Cohrs, Victoria L.
Abstract: We evaluated whether teaching tacts of images with or without backgrounds would affect acquisition during teaching and generality across untaught targets with four children diagnosed with autism spectrum disorder. Including backgrounds could slow acquisition but bolster generality across other media containing backgrounds, whereas removing backgrounds may improve acquisition but result in poorer generality. Overall, acquisition rates were similar across conditions for three children, although one child displayed consistently slower acquisition during the background condition. We rarely observed generality to untaught targets when programming extinction, but embedding differential reinforcement or teaching additional images with backgrounds led to equally successful outcomes irrespective of initial teaching conditions. Teaching with or without backgrounds may result in marginal differences in acquisition of teaching and untaught targets, especially when arranging supplemental procedures during tests for generality. We discuss the importance of intrasubject replication, considerations when testing for generality, and implications for practice.